Papers of Neville Bonner - Bonner, Neville, 1922-1999. (1934)
MS 7903 comprises correspondence, diaries, newscuttings, photographs, speeches, notes, subject files and other papers relating to Bonner's career as a senator and Aboriginal leader. The collection includes a large quantity of material relating to Aboriginal affairs, in addition to material on Bonner's personal life and his involvement in the One People of Australia League (OPAL) (57 boxes, 1 fol. box).
The Acc97.142 instalment comprises correspondence, greeting cards, business cards, invitations, travel documents, appointment diaries, publications, cuttings, speeches, financial papers, election papers, and a reel-to-reel tape of speeches, 1983 (32 boxes).
The Acc06.205 instalment comprises a range of loose and filed papers including electoral statistics, Bonner's first question and maiden speech, 1971, correspondence with colleagues and constituents, programs and invitations, newspaper clippings, photographs taken in Papua New Guinea in 1973, and material relating to the Neville Bonner Memorial Scholarship. There is also correspondence relating to the Trotter family (9 boxes).
Manuscript reference no.: MS 7903, MS Acc97.142, MS Acc06.205.
Guide to collections of manuscripts relating to Australia
National Library of Australia Oral History collection ORAL TRC 4900/64.
Politician. Neville Thomas Bonner was the first Australian Aboriginal to sit in federal parliament, as a Queensland Liberal Senator from 1971 to 1983. In 1979 Bonner was chosen as Australian of the Year, and, in 1984, he was appointed an Officer of the Order of Australia (AO) for service to politics and government. Following political life, Bonner served with many organisations, on the board of directors of the Australian Broadcasting Corporation, as chairman of the Indigenous Advisory Council and member of the Griffith University Council. He was awarded an honorary doctorate by Griffith University in 1993. As an author, Bonner wrote on indigenous matters as well as two publications for World Vision Australia: Equal world, equal share (1977) and For the love of children (1982).
Finding aid available in the Special Collections Reading Room and online at: http://www.nla.gov.au/ms/findaids/7903.html
Keywords: Bonner, Neville, -- 1922-1999 -- Archives; Liberal Party of Australia -- Officials and employees -- Archives; OPAL; Politicians -- Australia -- Archives; Aboriginal Australians -- Archives; Aboriginal Australians -- Politics and government; Aboriginal Australians -- Social conditions; Aboriginal Australians -- Legal status, laws, etc; Aboriginal Australians -- Government relations; Australia -- Politics and government -- 1972-1975.; Australia -- Politics and government -- 1976-1990.; Federal politicians; Authors